Why don't households see the light? Explaining the diffusion of compact fluorescent lamps - Bradford F. Mills; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2008)
Many countries are currently considering bans on incandescent light bulbs and other policies to enhance the residential diffusion of energy-saving compact fluorescent lamps (CFLs). However the reasons for currently limited diffusion of CFLs are largely unknown. This paper employs a Double Hurdle model to identify distinct barriers to household consideration of CFLs and the subsequent intensity of adoption using a large survey of German households. The results reveal that barriers to CFL consideration are low for all, except households with very low incomes. Further, barriers to CFL consideration are strongly linked to the characteristics of the residences of low-income households. Thus, the greatest potential for increasing the diffusion of CFLs lies not in addressing barriers to consideration, but in augmenting the intensity of household adoption particularly within high income groups.
urn:nbn:de:0011-n-840564
Keywords: 330